DEVELOPMENT AND VALIDATION OF UV-SPECTROSCOPIC METHOD FOR ESTIMATION OF TIOTROPIUM BROMIDE IN API AND PHARMACEUTICAL DOSAGE FORM - KOKANE, ANJALI P.; SHINDE, BHAGYASHRI S.; KALSHETTI, M. S. (International Journal of Current Pharmaceutical Research, 2020)
Objective: The current work intended towards the developed and validated UV spectrophotometric method for the estimation of Tiotropium Bromide in API and pharmaceutical formulation. Methods: The UV spectrum of tiotropium bromide in methanol shows maximum absorbance at 230 nm. Calibration curve method was used for the estimation of tiotropium bromide in API and pharmaceutical formulation. Results: Maximum absorbance obtained in 230 nm. Calibration curve plotted in concentration range 20-120 µm/ml exhibit the linearity relationship with line equation y=0.0057x+0.3319. The Accuracy was found to be 80-100.5%. The precision %RSD=0.1110, and the limit of detection(LOD)=4.12and limit of quantification (LOQ= 12.50. The method was found to comply all the validation parameters as per the ICH guideline in indicating the sensitivity of the method analyte. Conclusion: This method is used as satisfactory for the routine analysis of tiotropium bromide in API and pharmaceutical dosage forms.